2012
DOI: 10.1159/000333839
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Relative Low-Frequency Bilateral Globus Pallidus Internus Stimulation for Treatment of Cervical Dystonia

Abstract: Objective: To assess the effect of relative lower amplitude and frequency for globus pallidus internus (GPi) deep brain stimulation (DBS) of cervical dystonia (CD). Materials and Methods: Between February 2005 and October 2008, 14 patients diagnosed with CD underwent bilateral GPi DBS and all the patients received low-frequency stimulation and were followed for more than 2 years. We activated the implantable pulse generator 3–4 days postoperatively and initial amplitude, pulse width, and frequency were set at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In recently published study, low‐amplitude stimulation is appropriate to attain a sustained clinical and functional control of segmental dystonia . Our previous report also suggested that the initial setting as lower parameter after DBS surgery is most important to maintain other benefits in cervical dystonia . Patient who started with higher setting sometimes experienced stimulation‐induced side effects, or early depletion of implanted pulse generator (IPG).…”
Section: Discussionmentioning
confidence: 99%
“…In recently published study, low‐amplitude stimulation is appropriate to attain a sustained clinical and functional control of segmental dystonia . Our previous report also suggested that the initial setting as lower parameter after DBS surgery is most important to maintain other benefits in cervical dystonia . Patient who started with higher setting sometimes experienced stimulation‐induced side effects, or early depletion of implanted pulse generator (IPG).…”
Section: Discussionmentioning
confidence: 99%
“…After 6 months of non-blinded stimulation the mean pain reduction was 52% (p < 0.001), which was higher than the reduction in dystonia symptom severity (28%). In addition, nine case series (n = 6-14) showed a mean pain improvement from 48% to 73% which remained stable at follow-up ranging between 12 and 64 months [12,[18][19][20][21][22]. No correlations between motor and pain outcome were reported, but six case series highlighted a dissociation between motor and pain response in timing and/or the extent [11,12,19,21,23,24].…”
Section: Inherited and Idiopathic Dystoniamentioning
confidence: 94%
“…Low-frequency stimulation reduced the clinical myoclonus, which is also not consistent with the results of previous studies. While the mechanism underlying the improvement of myoclonus with low-frequency stimulation remains unclear, some studies proposed that low-frequency stimulation of the Gpi might also be effective for the treatment of dystonia [ 31 , 32 , 33 , 34 , 35 ]. Although a mean firing rate of the Gpi during an operation does not represent an optimal frequency of stimulation, Starr et al demonstrated a mean firing rate of the Gpi of 50 Hz in intraoperative MER of Gpi neurons in patients undergoing pallidal surgery for dystonia [ 36 ], and Alterman et al suggested that low-frequency stimulation may approximate the intraoperative firing rate of the target neurons [ 33 ].…”
Section: Discussionmentioning
confidence: 99%